KOMODIFIKASI AGAMA-AGAMA DI KOREA SELATAN - Saiful Hakam; Cahyo Pamungkas; Erni Budiwanti (Research Center for Regional Resources-Indonesian Institute of Sciences (P2SDR-LIPI), 2016)
The commodification of religions in South Korea reveals how religious aspects are commercialized and become a very dynamic marketplace. The commodification of religions reinforces the notion that religions is still strongly significant in the era of post-modern and neo-liberalism. Religions increasingly present in the public space and marketplace in South Korea. In the context of Buddhism, the commodification of religions has changed Buddhist temples, monasteries, and rituals become attractive and massive tourist destination. In the context of Christianity, commodification shows how church institutions utilize science of marketing and management in managing the churchs and the rituals in line with the interests of conggregation. Thirdly, in the context of Islam, the doctrine of halal increasingly to be institutionalized in the Islamic world has prompted the Korean food industries producing halal products for export to Islamic countries that are a potential and big market.AbstrakKomodifikasi agama di Korea Selatan mengungkapkan bagaimana aspek-aspek agama dikomersialkan dan menjadi pasar yang menarik. Komodifikasi agama memperkuat pandangan bahwa agama masih signifikan dalam era post-modern dan neo-liberalisme. Agama semakin hadir di ruang publik dan ruang pasar di Korea Selatan. Dalam konteks agama Budha, komodifikasi agama telah mengubah vihara, kehidupan vihara dan ritual Budha menjadi obyek pariwisata menarik sehingga menopang pariwisata Budha secara masif. Dalam konteks agama Kristen, komodifikasi memperlihatkan bagaimana institusi gereja memanfaatkan ilmu manajemen dan marketing dalam mengelola gereja dan menjalankan ritual sehingga lebih sesuai dengan minat jemaat. Ketiga, dalam konteks Islam, doktrin halal di dunia Islam telah mendorong industri makanan Korea Selatan memproduksi produk-produk halal untuk diekspor ke negara-negara Islam yang merupakan pangsa pasar potensial.